PERSEPSI MAHASISWA TERHADAP PENGGUNAAN CHATGPT PADA MATA KULIAH PEMODELAN MATEMATIKA - Garasut, Novresilia; Wenas, John Robby; Maukar, Marvel Grace (SOSCIED, 2024)
Artificial intelligence (AI) such as ChatGPT is applied in education as a tool in the learning process that plays a role in increasing access to information quickly and directly, so that students can more easily understand the material. The use of ChatGPT in modeling courses is triggered by satisfactory learning results, and in the learning process it is more time efficient and makes it easier for students to understand complex material in mathematical modeling courses. This research was conducted at Universitas Negeri Manado on students of the Mathematics Education Study Program, using a qualitative approach. Data were collected through questionnaires distributed online, as well as documentation of student learning outcomes with data analysis using a Likert Scale to measure student perceptions, including comfort of use, quality of information, and motivation to learn, evaluate, and use technology. The results showed that students benefited in the learning process due to the quick and relevant information from ChatGPT, as well as its ability to provide detailed answers. ChatGPT is considered to help their understanding in dealing with abstract concepts that often appear in mathematical modeling. On the other hand, students feel that the use of this AI still requires direct support from lecturers, especially for tasks that require critical and independent thinking. Although ChatGPT cannot replace the lecturer's role completely, its presence is supported to complement learning in a more efficient and interactive way, and allow students to learn more independently and actively